2012
DOI: 10.1007/s00330-012-2706-9
|View full text |Cite
|
Sign up to set email alerts
|

Digital X-ray radiogrammetry of hand or wrist radiographs can predict hip fracture risk—a study in 5,420 women and 2,837 men

Abstract: ObjectivesTo assess whether digital X-ray radiogrammetry (DXR) analysis of standard clinical hand or wrist radiographs obtained at emergency hospitals can predict hip fracture risk.MethodsA total of 45,538 radiographs depicting the left hand were gathered from three emergency hospitals in Stockholm, Sweden. Radiographs with insufficiently included metacarpal bone, fractures in measurement regions, foreign material or unacceptable positioning were manually excluded. A total of 18,824 radiographs from 15,072 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
16
3
Order By: Relevance
“…Previous studies have shown DXR-BMD measurements to predict hip, spine and other fractures to a similar degree as other peripheral BMD measurements [12–15]. Furthermore, DXR-BMD did also predict osteoporosis as measured by central DXA [15–17].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies have shown DXR-BMD measurements to predict hip, spine and other fractures to a similar degree as other peripheral BMD measurements [12–15]. Furthermore, DXR-BMD did also predict osteoporosis as measured by central DXA [15–17].…”
Section: Introductionmentioning
confidence: 71%
“…DXR can be performed on hand images acquired with any digital X-ray machine including those used for digital mammography. This means that DXR can be opportunistically integrated in existing mammography screening workflows with small impact on the workflow [11], or used to automatically process all forearm fracture images [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Digital X-ray radiogrammetry (DXR) is a feasible method which calculates cortical BMD in the metacarpal bones from plain X-rays [13,14]. Assessment by this method has revealed a significant reduction in DXR-BMD in patients with distal radius fracture compared with individuals in the general population and has been shown to be a predictor and risk factor for distal radius fracture and hip fracture [15-17]. The primary aim of the present study was to explore if there also is an association between reduced cortical hand BMD measured with DXR and fracture severity.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, DXR has proved a useful tool in adults as a predictor of long-term outcomes in rheumatoid arthritis and fracture prediction. 85,86 In children there are DXR reference data published, 87 and the technique has been applied to fracture prediction and the study of normal bone growth and development, and the differences between patient groups and healthy children. More recently, DXR has been combined with automated bone age assessment; in the BoneXpert system a pediatric bone index is provided 88 whose clinical value is still to be established.…”
Section: Digital X-ray Radiogrammetrymentioning
confidence: 99%